2021
DOI: 10.2147/imcrj.s343806
|View full text |Cite
|
Sign up to set email alerts
|

Belly Dancer Dyskinesia During Pregnancy: Case Report from Harar, Eastern Ethiopia

Abstract: Introduction: Belly dancer dyskinesia (BDD) is an involuntary waving and writhing type of abdominal wall movement, which resemble those of a belly dancer. Worldwide only four cases of belly dancer dyskinesia during pregnancy were reported. In two of the reported cases, it has recurred in the succeeding pregnancy while the remaining one did not mention about the recurrence. I am reporting a 25 year old primigravida woman with gestational age of 25 weeks plus 6 days presented with involuntary, rhythmic and painf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…BDD in pregnancy is even rarer, there have only been five reported cases. [4][5][6][7] Currently, there is limited study regarding this condition, and our patient would be the second reported case from Ethiopia.…”
Section: Introductionmentioning
confidence: 94%
“…BDD in pregnancy is even rarer, there have only been five reported cases. [4][5][6][7] Currently, there is limited study regarding this condition, and our patient would be the second reported case from Ethiopia.…”
Section: Introductionmentioning
confidence: 94%
“…[3][4][5][6] During pregnancy and post-partum periods, its occurrence has been attributed to thoracic cord compression by the gravid uterus. 7 Centrally, the respiratory center of the rostral medulla has also been implicated in its pathophysiology. 4 Even though the diagnosis is always clinical, it can be supported by fluoroscopy and diaphragmatic electromyogram (EMG) showing rhythmic contractions of the diaphragm.…”
Section: Introductionmentioning
confidence: 99%
“…Belly dancer's dyskinesia (BDD) is a rare disorder characterized by involuntary movements of the abdominal wall 1,2 . We present a rare case of a pregnant woman with BDD; only five similar cases have been reported.…”
mentioning
confidence: 99%
“…Three hypotheses exist for the etiology of abnormal abdominal movements in BDD of pregnancy: (1) gravid uterus compresses the spinal cord, (2) vitamin B12 deficiency, and (3) irritation of the phrenic nerve 2–4 …”
mentioning
confidence: 99%
See 1 more Smart Citation